2022
DOI: 10.3389/fgene.2022.815727
|View full text |Cite
|
Sign up to set email alerts
|

SNP–SNP Interactions of Surfactant Protein Genes in Persistent Respiratory Morbidity Susceptibility in Previously Healthy Children

Abstract: We studied associations of persistent respiratory morbidity (PRM) at 6 and 12 months after acute respiratory failure (ARF) in previously healthy children with single-nucleotide polymorphisms (SNPs) of surfactant protein (SP) genes. Of the 250 enrolled subjects, 155 and 127 were followed at 6 and 12 months after an ARF episode, respectively. Logistic regression analysis and SNP–SNP interaction models were used. We found that 1) in the multivariate analysis, an increased risk at 6 and 12 months was associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…One of its SNPs, rs1136450, was the most frequently observed SFTPA1 SNP in the 3-SNP interactions. This SNP was found to be significant either by itself, as part of significant haplotypes, or part of significant 3-SNP interactions and has been found previously to associate with susceptibility with other pulmonary diseases including community acquired pneumonia ( 61 ), cystic fibrosis ( 47 ), acute respiratory distress of the newborn ( 59 ) and pediatric acute and chronic respiratory failure ( 58 , 62 ). The rs1136450 SNP encodes (leu/val) amino acid 50 (AA50), and it is located within the collagen-like region of SP-A1.…”
Section: Discussionmentioning
confidence: 71%
“…One of its SNPs, rs1136450, was the most frequently observed SFTPA1 SNP in the 3-SNP interactions. This SNP was found to be significant either by itself, as part of significant haplotypes, or part of significant 3-SNP interactions and has been found previously to associate with susceptibility with other pulmonary diseases including community acquired pneumonia ( 61 ), cystic fibrosis ( 47 ), acute respiratory distress of the newborn ( 59 ) and pediatric acute and chronic respiratory failure ( 58 , 62 ). The rs1136450 SNP encodes (leu/val) amino acid 50 (AA50), and it is located within the collagen-like region of SP-A1.…”
Section: Discussionmentioning
confidence: 71%
“…A total of 16 target SNPs of SP genes, SFTPA1 , SFTPA2 , SFTPB , SFTPC , and SFTPD were selected that included, 5 SNPs from SFTPA1 , rs1059047, rs1136450, rs1136451, rs1059057, and rs4253527; 4 SNPs from SFTPA2 , rs1059046, rs17886395, rs1965707, and 1965708; 3 SNPs from SFTPB , rs2077079, rs3024798, and rs1130866; 2 SNPs from SFTPC , rs4715 and rs1124; and 2 SNPs from SFTPD , rs721917 and rs2243639. Several acute and chronic pulmonary diseases of all age groups, such as, neonatal RDS ( 31 35 ), CF ( 36 ), COPD ( 37 , 38 ), ARDS ( 23 ), hypersensitivity pneumonitis ( 39 , 40 ), pediatric ARF ( 41 ), and persistent respiratory morbidity in pediatric ARF survivors ( 42 ) have been shown to be associated with the studied SNPs. The SP-A1 (6A, 6A m , m=0-13) and SP-A2 (1A, 1A n , n=0-15) genotypes were assigned as described ( 19 ).…”
Section: Methodsmentioning
confidence: 99%
“…Several acute and chronic pulmonary diseases of all age groups, such as, neonatal RDS (31)(32)(33)(34)(35), CF (36), COPD (37,38), ARDS (23), hypersensitivity pneumonitis (39,40), pediatric ARF (41), and persistent respiratory morbidity in pediatric ARF survivors (42) have been shown to be associated with the studied SNPs. The SP-A1 (6A, 6A m , m=0-13) and SP-A2 (1A, 1A n , n=0-15) genotypes were assigned as described (19).…”
Section: Selection Of Genetic Variantsmentioning
confidence: 99%
See 1 more Smart Citation
“…These SNPs have been shown to associate with various acute and chronic pulmonary diseases, such as cystic fibrosis, 7 acute respiratory distress syndrome, 8 neonatal respiratory distress syndrome (RDS), 9 hypersensitivity pneumonitis, 10 interstitial pulmonary fibrosis, 11 the severity of respiratory syncytial virus (RSV) 12 and tuberculosis (TB) 13 . We showed that SNP‐SNP interactions among SP genes are associated with pediatric ARF and its short‐ 14 and long‐term outcomes 15 . However, these interactions do not provide any information about the contribution of individual SNPs in the given interaction.…”
Section: Introductionmentioning
confidence: 99%